Usage of meta- Synthesis methodology in analyzing paradigm shifts based on spiritual urbanism approach - Farzaneh madani; Afson Mahdavi; mojtaba rafiyan; Fatemeh Mohammad Niae Qaraee (تحقیقات کاربردی علوم جغرافیایی)
Spiritual-led urbanism is being structured as a new paradigm in urban planning. Social inequality, polarization, moral poverty, and a high prevalence of psychiatric disease are only part of the manifestation of the lack of attention to the issue of spirituality in the production of space. Indeed, the challenge of the contemporary city is the emergence of the process of personalization of space production and capitalization resulting from the dominance of the speculative model and its confrontation with identity and semantic structure. In contrast to these challenges, the discussion of spirituality in recent decades by prominent Harvard scholars has emerged as an interdisciplinary paradigm, embedded in a powerful stream of critical communication planning theory and requiring context. Therefore, the present article analyzes the theoretical field of research related to the paradigm of spiritual development in the production of urban space. This article is based on a combination and is meta synthesis. The statistical population of the study consists of 55 ISI and scientific-research articles in the period 2008-2019. In order to collect and data analyze, methods such as systematic review and open coding have been used. In this context, comprehensive form for summarizing and extracting data from selected research was developed which issues concerning public profile and the theoretical framework of the research. The research findings are presented in two parts: structural and content. The first section examines the general features of selected research, the unreliability of studies on the impact of spirituality on urban space production, and the second section elaborates on the theoretical framework of research on spatial spirituality. production of spiritual-